Multiphysics modeling of a magnetoelectric composite Rosen-type device. (March 2016) - Talleb, Hakeim; Gensbittel, Aurélie; Ren, Zhuoxiang
Abstract: This paper presents the multiphysics modeling of a Rosen-type device using a magnetoelectric (ME) composite, which has hybrid sensor and energy transducer functions. The modeling of such a multiphysics problem involves magnetic, mechanical and magnetic phenomena and is strongly coupled using the finite element method (FEM). To take into account the impact of the impedance connected to the device ports, the system equation is also coupled to the electrical circuit equation. A good concordance is obtained in harmonic regime between the simulation results and the experiment ones available in the literature. The simulation results put in evidence that the input impedance of the dynamic signal analyzer, when it is used to monitor the output voltage of the sensor part, implicates an alteration of the frequency resonance. The high output voltage coefficient of the sensor and the significant deliverable power of the energy transducer make the ME Rosen-type device an ideal candidate for hybrid magnetic sensing and energy harvesting or wireless powering applications.